Update on epidemiology of hepatitis B and C in China - Cui, Yan; Jia, Jidong (Journal of gastroenterology and hepatology, 2013)
A high rate of chronic hepatitis B virus (HBV) infection in China is mainly caused by perinatal or early childhood transmission. Administration of universal HBV vaccination in infants has led to a dramatic decrease in HBV epidemiology, with hepatitis B surface antigen (HBsAg) prevalence declining from 9.75% in 1992 to 7.18% in 2006. The major HBV genotypes are B and C, with B being more prevalent in the southern part and C more prevalent in the northern part of China. A national survey carried out in 1992 showed that the hepatitis C virus (HCV) infection rate was 3.20% in general population in China. After implementation of mandatory HCV screening for blood transfusion and other precautions to prevent blood‐borne disease since 1993, the new cases of HCV infection associated with blood or blood product has become very rare. Although the anti‐HCV prevalence would be much higher in high‐risk groups, a survey carried in 2006 showed that the anti‐HCV prevalence rate was only 0.43% in general population. This sharp decline in HCV infection rate was mainly due to stringent administration and monitoring of blood donors and blood products, but may also be related to the remarkably improved specificity of anti‐HCV test. The predominant HCV genotype in China is genotype 1b (60–70%), and the host interleukin‐28b rs12979860 CC genotype is very frequent in Chinese population (over 80%).